Eu cuido dela e ela me cuida: um estudo qualitativo sobre o cuidado intergeracional com o idoso - Flores, Gisela Cataldi (2008)
Populational aging is a heterogeneous worldwide social phenomenon. In Brazil, it has happened fast, generating a social demand for families, society, and the nation, which must handle it. The chosen research orientation was a qualitative one, with an ethnographic approach, aiming to interpret the intergenerational care with the elderly living in an area under the scope of the Family Health Strategy in the city of Santa Maria, Rio Grande do Sul state, respecting their cultural particularities. Theoretical references used include Clifford Geertz and Madaleine Leininger, among others. Data analysis followed Laurence Bardin, which works with content analysis, and Marcel Mauss was crucial for the detailing of the reciprocity concept. Also used was the referential of Lorraine M. Wright and Maureen Leahey, who state that the genogram is a particularly useful instrument to be employed by the nurse, characterized as a diagram of the family group. Through data analysis, the topic of reciprocity appeared as a structuring element in the care of the elderly. The notion of reciprocity is examined in detail, considering the behaviors, attitudes, values and beliefs of the elderly and their caregivers from other generations. The care of the elderly by other generations is thought to be an opportunity of co-accountability regarding their care and populational aging. In this sense, intergenerational actions are proposed with informal and formal caregivers.